Mesencephalic astrocyte-derived neurotrophic factor is an ER-resident chaperone that protects against reductive stress in the heart - Arrieta, Adrian; Blackwood, Erik A.; Stauffer, Winston T.; Domingo, Michelle Santo; Bilal, Alina S.; Thuerauf, Donna J.; Pentoney, Amber N.; Aivati, Cathrine; Sarakki, Anup V.; Doroudgar, Shirin; Glembotski, Christopher C. (The journal of biological chemistry, 2020)
We have previously demonstrated that ischemia/reperfusion (I/R) impairs endoplasmic reticulum (ER)-based protein folding in the heart and thereby activates an unfolded protein response sensor and effector, activated transcription factor 6α (ATF6). ATF6 then induces mesencephalic astrocyte-derived neurotrophic factor (MANF), an ER-resident protein with no known structural homologs and unclear ER function. To determine MANF's function in the heart in vivo, here we developed a cardiomyocyte-specific MANF-knockdown mouse model. MANF knockdown increased cardiac damage after I/R, which was reversed by AAV9-mediated ectopic MANF expression. Mechanistically, MANF knockdown in cultured neonatal rat ventricular myocytes (NRVMs) impaired protein folding in the ER and cardiomyocyte viability during simulated I/R. However, this was not due to MANF-mediated protection from reactive oxygen species generated during reperfusion. Because I/R impairs oxygen-dependent ER protein disulfide formation and such impairment can be caused by reductive stress in the ER, we examined the effects of the reductive ER stressor DTT. MANF knockdown in NRVMs increased cell death from DTT-mediated reductive ER stress, but not from nonreductive ER stresses caused by thapsigargin-mediated ER Ca2+ depletion or tunicamycin-mediated inhibition of ER protein glycosylation. In vitro, recombinant MANF exhibited chaperone activity that depended on its conserved cysteine residues. Moreover, in cells, MANF bound to a model ER protein exhibiting improper disulfide bond formation during reductive ER stress but did not bind to this protein during nonreductive ER stress. We conclude that MANF is an ER chaperone that enhances protein folding and myocyte viability during reductive ER stress.
Gesehen am 31.08.2020